Immune functions of pattern recognition receptors in Lepidoptera - Zhao, Lin; Niu, Jinlan; Feng, Disong; Wang, Xialu; Zhang, Rong (Frontiers in Immunology, 2023)
Pattern recognition receptors (PRRs), as the “sensors” in immune response, play a prominent role in recognizing pathogen-associated molecular patterns (PAMPs) and initiating the effective defense response to pathogens in Lepidoptera. It is becoming increasingly important that damage-associated molecular patterns (DAMPs) normally play a physiological role within cells, however, when exposed to extracellular, they may become “part-time” critical signals of the immune response. Based on the research in recent years, we reviewed the typical PRRs of Lepidoptera, including peptidoglycan recognition protein (PGRP), gram-negative binding protein (GNBP), β-1,3-glucan recognition protein (βGRP), C-type lectin (CTL), and Scavenger receptor (SR). We also outlined the ways in which DAMPs participated in the immune response, and the correlation between PRRs with immune escape. Taken together, these data suggest that the role of PRRs in insect innate immunity may be much greater than expected and that it is possible to recognize a broader range of signaling molecules.